Rediscovery of Mus nitidulus Blyth (Rodentia: Muridae), an endemic murine rodent of the central basin of Myanmar - Shimada, Tomofumi; Aplin, Kenneth P.; Jenkins, Paulina; Suzuki, Hitoshi (Zootaxa, 2007)
A genetically distinct population of mice from south central Myanmar is identified as Mus nitidulus Blyth, a taxon described in 1859 but subsequently treated as a synonym of a more widely distributed Asian mouse—Mus cervicolor Hodgson, 1845. We present molecular sequence data from mitochondrial and nuclear genes which demonstrate that M. nitidulus is distinct from M. cervicolor and from all other species of Mus currently recognized in the Asian region. The molecular data further show that M. nitidulus is a member of the Mus booduga Species Group within subgenus Mus, and thus phylogenetically remote from M. cervicolor. We stabilize the nomenclature of M. nitidulus by designating a lectotype with associated molecular sequence data. We review and illustrate the morphology of M. nitidulus and reassess all previously referred material. Mus nitidulus appears to be confined to the central basin of Myanmar, an area that formerly supported a mosaic of evergreen and deciduous monsoon forests. Today, this region is largely cleared and employed for rainfed rice cultivation. Mus nitidulus is only the second mammal species recorded as endemic to Myanmar. It can be locally abundant in ricefield habitat and is regarded locally as an agricultural pest.